Central African Republic : Third Review under the Extended Credit Facility Arrangement, Requests for Waiver of Nonobservance of Performance Criterion, Modification of Performance Criteria, Augmentation of Access, and Financing Assurances Review-Press Release; Staff Report; and Statement by the Executive Director for the Central African Republic. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Central African Republic's Third Review Under the Extended Credit Facility (ECF) Arrangement, Requests for Waiver of Nonobservance of Performance Criterion, Modification of PCs, Augmentation of Access, And Financing Assurances Review. Program performance through end-June has been satisfactory. All quantitative criteria and indicative targets were met, with the exception of the domestic revenue target for which the authorities are taking corrective actions and a waiver of nonobservance was granted. All structural reforms have been implemented, albeit with some delays. The IMF staff supports completion of the third review under the ECF arrangement and the waiver of nonobservance of PCs on domestic revenue, on the basis of the corrective actions taken.